Assessing the Benthic Ecological Quality in the Intertidal Zone of Cheonsu Bay, Korea, Using Multiple Biotic Indices - Liang, Jian; Ma, Chae-Woo; Kim, Seon-Kyu; Park, Sang-Hyeok (Water (Basel), 2024)
With the growing global focus on marine environmental conservation and management, it is imperative to evaluate the ecological quality of marine ecosystems accurately. In this study, we employed seven biotic indices, namely the AZTI marine biotic index (AMBI), BENTIX, benthic opportunistic polychaetes amphipods index (BOPA), benthic pollution index (BPI), multivariate AZTI marine biotic index (M-AMBI), abundance biomass comparison (W-value), and Shannon diversity index (H’), to assess the benthic ecological quality in the intertidal zone of Cheonsu Bay, South Korea. Except for the H’ and W-value, the indices (AMBI, BENTIX, BOPA, BPI, and M-AMBI) suggest that the ecological quality at most stations in the intertidal zone of Cheonsu Bay was acceptable. Furthermore, the influx of a large amount of eutrophic freshwater has impacted the intertidal zone of Cheonsu Bay, but the applicability of the seven biotic indices requires further investigation.